2009
DOI: 10.1037/a0016315
|View full text |Cite
|
Sign up to set email alerts
|

Prospective relations between growth in drinking and familial stressors across adolescence.

Abstract: Although there is much empirical support for the relation between stress and alcohol consumption in adolescence, it is unclear whether exposure to stressors is associated with overall trajectories or temporary elevations in drinking. Moreover, little research has explored whether the stress-alcohol use association in adolescence may be explained by shared risk factors that produce both individual differences in stress exposure and elevated risk for alcohol use. The current study tested these hypotheses within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 81 publications
1
30
0
Order By: Relevance
“…Though this theory has dominated the PTSD-alcohol literature, as noted, the evidence for a self-medication pathway has been limited when tested in adolescent and college samples (e.g., Colder & O’Connor, 2005; Colder et al, 2010; Ham et al, 2009; King, Molina, & Chassin, 2009; Read et al, 2012; Read & O’Connor, 2006). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though this theory has dominated the PTSD-alcohol literature, as noted, the evidence for a self-medication pathway has been limited when tested in adolescent and college samples (e.g., Colder & O’Connor, 2005; Colder et al, 2010; Ham et al, 2009; King, Molina, & Chassin, 2009; Read et al, 2012; Read & O’Connor, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Findings from this work have been somewhat mixed. For example, King et al (2009) examined yearly assessments of both state and trait dimensions of family stress to predict latent alcohol trajectories during adolescence (ages 13–17). These authors found that state family stress was directly associated with alcohol use within each time point.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that stress in adolescence is related to health-risk behaviors, such as alcohol and other substance use (King, Molina, & Chassin, 2009;Wills, Sandy, Yaeger, Cleary, & Shinar, 2001), as well as smoking (Finkelstein, Kubzansky, & Goodman, 2006). A study of 451 adolescents, ages 13-17 years, with alcoholic parents and a matched control found that stressors were related to adolescents' alcohol use and predicted short-term increases in use (King, Molina, & Chassin, 2009).…”
Section: Stress Outcomesmentioning
confidence: 99%
“…A study of 451 adolescents, ages 13-17 years, with alcoholic parents and a matched control found that stressors were related to adolescents' alcohol use and predicted short-term increases in use (King, Molina, & Chassin, 2009). Stress has also been associated with poor dietary habits in adolescents.…”
Section: Stress Outcomesmentioning
confidence: 99%
“…Adolescent alcohol or stress exposure can dramatically promote future alcohol intake both in humans (Dawson et al 2007;Enoch 2011;King et al 2009;Pilowsky et al 2009) and in preclinical rodent models (Fullgrabe et al 2007;Schramm-Sapyta et al 2008;Spear and Varlinskaya 2010;Wills et al 2010). Adolescence is thus a time of particular risk and an important period for targeted intervention.…”
Section: Targeting Adolescence As a Time For Learning Emotional Skillsmentioning
confidence: 99%